2004
DOI: 10.1111/j.1365-3156.2004.01230.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of treatment for tuberculosis: a randomized controlled trial of community health workers versus family members

Abstract: SummaryWe implemented community-based direct observation of treatment, short course (DOTS), including a randomized controlled trial of direct observation either by community health workers (CHWs) or family members, under operational conditions in a region of Swaziland. There was a high death rate of 15%, due to the high HIV rates in the region. There was no significant difference in the cure and completion rate between direct observation of treatment by CHWs and family members [2% difference (95% CI )3% to 7%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(81 citation statements)
references
References 13 publications
(25 reference statements)
3
76
0
2
Order By: Relevance
“…It is true that some small pilot projects (none of which have monitored relapse or development of drug resistance) using family observation, combined with intensive supervision and home visits, have achieved high cure rates. [12][13][14] However, other studies have reported that family observation yields lower cure rates and much higher default rates than observation by someone outside the family, 15 and results in a substantial proportion of treatment being unobserved and much higher rates of non-adherence. In practice, where family observation is allowed, patients are often merely handed medicines and told to have their spouse watch them take the pills, a practice that is inconsistent with WHO guidelines specifying that treatment observers be trained and supervised by the health-care system.…”
Section: Family Observation Is a Seductive But Risky Conceptmentioning
confidence: 87%
“…It is true that some small pilot projects (none of which have monitored relapse or development of drug resistance) using family observation, combined with intensive supervision and home visits, have achieved high cure rates. [12][13][14] However, other studies have reported that family observation yields lower cure rates and much higher default rates than observation by someone outside the family, 15 and results in a substantial proportion of treatment being unobserved and much higher rates of non-adherence. In practice, where family observation is allowed, patients are often merely handed medicines and told to have their spouse watch them take the pills, a practice that is inconsistent with WHO guidelines specifying that treatment observers be trained and supervised by the health-care system.…”
Section: Family Observation Is a Seductive But Risky Conceptmentioning
confidence: 87%
“…However, the improved outcomes of the intervention group could be attributed to the increased frequency of a visit by a CHW. Because it was already shown that direct observation for DOTS can be successfully undertaken by either a family member or a CHW, 11,12 a larger follow-up study to our pilot should segregate daily supervision by a CHW from daily supervision by a CHW using eCompliance to determine the added impact of the biometric monitoring tool.…”
Section: Discussionmentioning
confidence: 99%
“…10 Directly observed therapy (DOT) is another potential approach for treatment supporters to promote ART adherence, based on the efficacy of community-based DOT for tuberculosis administered by family members or guardians. [11][12][13] Our collaborative research group conducted a randomized, controlled trial that compared partial DOT administered by trained patient-nominated treatment supporters (DOT-ART) to self-administered ART (Self-ART) in ART-naïve adult patients with treatment supporters in South Africa. 14 There was no significant difference between the groups in the proportion of patients with undetectable viral load or median CD4 cell count increase persisting beyond 6 months.…”
Section: Introductionmentioning
confidence: 99%